Nilai-Nilai Moderasi Beragama Dalam Film Kebun Krecek Di Channel Youtube Krecek Media (Analisis Semiotika Roland Barthes) - Cucu Indah Sari; Khusnul Khotimah Khotimah (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2022)
Religious moderation is one of the efforts to deal with differences in religion. Religious moderation can be manifested in a moderate attitude in dealing with cultural, ethnic, taste and religious differences. Religious moderation can produce a harmonious, peaceful life order, and create a society that respects each other in the midst of existing differences. There are many media that can be used to convey messages of religious moderation, one of which is through film. This study aims to analyze the values of religious moderation contained in the film Kebun Krecek on the Krecek Media Youtube channel. The theory used in this study is Roland Barthes' semiotic theory to analyze signs through the processes of denotation, connotation and myth meanings. This research uses a qualitative descriptive approach. The results obtained from this study are that there are two actors/actors of different religions namely Hindus and Muslims who are still good friends and help each other even though they have different religions. The scenes in the film also represent the values of religious moderation that they apply in their daily life, namely the scene of lending a bicycle to a Muslim friend so they won't be late for Friday, sharing drinks and snacks, and inviting friends to eat together. at home.